Perbaikan Kualitas Pelayanan dengan Metode Integrasi Servqual dan Diagram Kartesius di Perusahaan Daerah Air Minum Tirta Moedal Semarang - Aldinar Assyafiq Akbar; Imam Nuryanto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to identify the service attributes that are important to consumers using the servqual integration method and cartesian diagrams. With the help of the SPSS tool, 120 respondents were surveyed. The results show that the quality of service provided by Tirta Moedal Water Company is good, with an average performance score of 3.5 on a scale of 1 to 5. The dimensions that need to be improved are responsiveness and empathy. These attributes include the process of handling complaints, providing information during maintenance, the speed of responding to customer complaints, the ability of employees to listen to customer complaints, and the availability of consultation and complaint services for consumers. This study is expected to help improve service quality and maintain existing attributes.